2017
DOI: 10.1111/nep.12749
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength, mobility, quality of life and falls in patients on maintenance haemodialysis: A prospective study

Abstract: Physical parameters appear to be associated with meaningful patient outcomes and showed measurable deterioration over relatively short time frames. Interventions, with the potential to slow physical decline in people receiving maintenance dialysis, such as exercise programmes, warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…Our findings on the robust, independent association between SPPB‐derived lower extremity function and mortality are consistent with previous reports of the association between the SPPB and dialysis risk in prevalent ESRD patients . Our study extends these findings from prevalent ESRD patients to KT recipients who are very highly selected from the dialysis population and who undergo an invasive procedure with subsequent immunosuppression.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings on the robust, independent association between SPPB‐derived lower extremity function and mortality are consistent with previous reports of the association between the SPPB and dialysis risk in prevalent ESRD patients . Our study extends these findings from prevalent ESRD patients to KT recipients who are very highly selected from the dialysis population and who undergo an invasive procedure with subsequent immunosuppression.…”
Section: Discussionsupporting
confidence: 91%
“…In our study age was an independent predictor of reduced HRQoL. This may be explained as a combination of the burden of kidney disease and aging in general, which is known to affect HRQoL …”
Section: Discussionmentioning
confidence: 48%
“…It is possible that the reduction in physical function and the loss of freedom is experienced differently for men than women in this elderly population . Both genders experience a worsened HRQoL during the first year on the waiting list suggesting that the waiting time and the reduced kidney function may itself be a burden …”
Section: Discussionmentioning
confidence: 99%
“…From a preventive and rehabilitative point of view, this syndrome is a potentially modifiable risk factor, as previous studies conducted in HD populations have shown that single frailty components, such as low physical activity, muscle strength, and slow gait speed can be improved following exercise-based interventions [11]. Although frailty has been consistently shown to be associated with falls in HD patients [4,12,13], few studies have explored the relationship between objective frailty-related physical function measures and falls [1,2,4,12,14,15]. Results from these studies seem to indicate that, in predicting falls, composite indices of physical function [14,15] may be more useful than single component assessments [2].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Although frailty has been consistently shown to be associated with falls in HD patients [4,12,13], few studies have explored the relationship between objective frailty-related physical function measures and falls [1,2,4,12,14,15]. Results from these studies seem to indicate that, in predicting falls, composite indices of physical function [14,15] may be more useful than single component assessments [2]. However, the identification of which individual frailty/ physical function components may be more closely associated with falls is of paramount importance, as this would eventually allow exercise-based rehabilitation programs to be tailored to reduce the occurrence of falls in CKD-5 patients on HD.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%